Design of Inventory Management System for Herat University Using Component-Based Methodology - Zabihi, Somaia (American International Journal of Social Science Research, 2019)
The focus of CBSD is to assemble the previously-existing software components and to develop new and large software systems with new characteristics. It emphasizes on the use of Off the Shelf (OTS) components instead of building a system from the scratch. The first objective of this thesis is to discuss about the Component-Based Software Development (CBSD) as one of the advanced methodologies with the example of an inventory management system for Herat University, in Afghanistan. The second objective examines more closely whether CBSD can be a proper approach in Afghanistan, particularly in context of Herat University Inventory Management System (HU-IMS).This paper only focuses on selected phases such as requirement analysis and system design of HU-IMS life cycle. JavaBeans component model and user requirement analysis formulate to design the two separate components of HU-IMS (User Management and Resource Management).Both components are designed in a general way as they either can join as a part of a pre-functional system such as Higher Education Management Information System (HEMIS) or to be used for the purpose to develop new software systems. The results of the thesis confirm that considering CBSD when designing HU-IMS can be a proper approach in the Afghanistan scenario. However, the CBSD, particularly in Afghanistan context, has its own challenges and risks as all other approaches have. Since there are not many localized libraries and repositories available, the first challenge is to find and select the proper component which can be difficult and time-consuming; and the second is the adaptation and localization of the found component insomuch as most of the software developers are unfamiliar with the emerging concept.